Effect of Nano Surface Topography on Electrical Properties of Lead Sulfide (PbS) Films Deposited on Polymer Substrate - Faraj, Mohammad Ghaffar (Journal of Technology Innovations in Renewable Energy, 2016)
Lead sulfide (PbS) films were deposited on polymide (PI) plastic substrate chemical spray pyrolysis technique at substrate temperature in the range 250-350 oC. Effects of substrate temperature on the electrical properties of the films were studied. In addition, the effect of nano surface topography on electrical properties of PbS films was studied. The deposited films were analyzed with atomic force microscope and Hall measurements to determine their electrical characteristics. AFM data shows that the root mean square (RMS) surface roughness of the PbS film increases with increasing substrate temperature. At room temperature, electrical resistivity of the PbS films varies from 9.54x103 to 1.14x103 Ω.cm, respectively.